2021
DOI: 10.3390/app11062824
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula Strains Isolated from Seawater That Can Biotransform Raw Glycerol into Docosahexaenoic Acid (DHA) and Carotenoids for Animal Nutrition

Abstract: Due to the overexploitation of industrial fisheries, as the principal source of fish oil, as well as the increasing replacement of synthetic pigments for animal nutrition, we need to find sustainable sources for these essential nutrient productions. Marine Rhodotorula strains NCYC4007 and NCYC1146 were used to determine the biosynthesis of docosahexaenoic acid (DHA) and carotenoids by biotransforming raw glycerol, a waste product of biodiesel. To evaluate the presence of inhibitory substances in raw glycerol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This yeast can also produce a range of valuable metabolites, including pigments, ergosterol, lipids, and polysaccharides (Byrtusová et al, 2021). Besides, Rhodotorula yeast is capable of producing isobutene (Fujii et al, 1987), antibacterial pathogens (Hartati et al, 2017;Vidya et al, 2022) Li, et al, 2022;Maza et al, 2020), bio-emulsifier (Oloke & Glick, 2005), plant growth promoters (Hartati et al, 2019), omega-3 fatty acids (Pino-Maureira et al, 2021), exopolysaccharides (Silambarasan et al, 2019), as well as biosurfactants (Gharaghani et al, 2019). The carotenoids produced by Rhodotorula yeast are increasingly being utilized as a replacement for synthetic carotenoids as supplements in poultry feed to increase poultry productivity (Grigore et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This yeast can also produce a range of valuable metabolites, including pigments, ergosterol, lipids, and polysaccharides (Byrtusová et al, 2021). Besides, Rhodotorula yeast is capable of producing isobutene (Fujii et al, 1987), antibacterial pathogens (Hartati et al, 2017;Vidya et al, 2022) Li, et al, 2022;Maza et al, 2020), bio-emulsifier (Oloke & Glick, 2005), plant growth promoters (Hartati et al, 2019), omega-3 fatty acids (Pino-Maureira et al, 2021), exopolysaccharides (Silambarasan et al, 2019), as well as biosurfactants (Gharaghani et al, 2019). The carotenoids produced by Rhodotorula yeast are increasingly being utilized as a replacement for synthetic carotenoids as supplements in poultry feed to increase poultry productivity (Grigore et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that the production of microbial lipids and carotenoids from waste frying oil (WFO) derived glycerol in Rhodotorula sp. had no inhibitory effects relative to pristine glycerol (Pino-Maureira et al., 2021 ). It is likely that differences in the waste stream, culture conditions, microbial host, or some combination are causing these discrepancies and warrant further investigation.…”
Section: Other Industrial Wastesmentioning
confidence: 99%
“…Pigmented Rhodotorula spp. strains that accumulated intracellular carotenoids were also isolated from seawater near Chile [ 234 ]. One of the strains accumulated carotenoids, representing 19% of its dry weight, when cultured in glycerol as the only carbon source.…”
Section: Main Marine Organisms Containing Carotenoidsmentioning
confidence: 99%